2006
DOI: 10.3201/eid1207.060127
|View full text |Cite
|
Sign up to set email alerts
|

Migratory Passerine Birds as Reservoirs of Lyme Borreliosis in Europe

Abstract: Birds host vector ticks and Borrelia species and vary in effectiveness as reservoirs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
195
5
16

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(232 citation statements)
references
References 36 publications
14
195
5
16
Order By: Relevance
“…Our finding that all four rooted clonal complexes of B. burgdorferi had ancestral genotypes found exclusively in coastal sites of the Northeast US is compatible with the explanation that if B. burgdorferi migrated from Europe to the US, it would have first arrived in the northeast and spread westward into its current range from there. It is unknown how B. burgdorferi might have been transported across the Atlantic before the arrival of Europeans in the New World, but it has been found in birds on both continents (46,47).…”
Section: Resultsmentioning
confidence: 99%
“…Our finding that all four rooted clonal complexes of B. burgdorferi had ancestral genotypes found exclusively in coastal sites of the Northeast US is compatible with the explanation that if B. burgdorferi migrated from Europe to the US, it would have first arrived in the northeast and spread westward into its current range from there. It is unknown how B. burgdorferi might have been transported across the Atlantic before the arrival of Europeans in the New World, but it has been found in birds on both continents (46,47).…”
Section: Resultsmentioning
confidence: 99%
“…A large-scale study from southeastern Sweden showed a 19.3% prevalence of B. burgdorferi s.l. in nymphs collected from birds (Comstedt et al 2006). In contrast, data from Central Europe showed higher B. burgdorferi s.l.…”
Section: Discussionmentioning
confidence: 99%
“…There are several studies reporting the presence of B. afzelii in bird-feeding ticks (Humair et al 1998, Comstedt et al 2006, Kipp et al 2006, Poupon et al 2006, Taragel'ova et al 2008, Franke et al 2010b), although B. afzelii is regarded to be a rodent-associated genospecies in Europe (Humair et al 1999, Hanincova et al 2003a). It has been previously shown that birds do not serve as adequate reservoirs for B. afzelii, and furthermore, that the uptake of avian blood initiates the elimination of B. afzelii in the tick (Kurtenbach et al 2002).…”
Section: Discussionmentioning
confidence: 99%
“…The list of potential reservoir hosts is great and variable and includes species in classes Mammalia, Aves, and Reptilia (9,15). The worldwide distribution of B. burgdorferi sensu lato may be caused by long-distance dispersal of infected birds that serve as hosts for ticks (11,46,53).…”
mentioning
confidence: 99%